The Effect of Financial Literacy and Inclusion on Personal Financial Management with Fintech as a Moderating Variable - Setyawati, Amelia (Journal of Applied Business, Taxation and Economics Research, 2025)
This study examines the role of financial technology (fintech) as a moderating variable in the relationship between financial literacy and financial inclusion on personal financial management among the productive age group in Malang City. The research approach used is explanatory quantitative with purposive sampling technique, resulting in 113 respondents who met the criteria. The data were analyzed using multiple regression analysis and Moderated Regression Analysis (MRA) with the help of SPSS 22. The results show that: (1) financial literacy has a positive and significant effect on personal financial management; (2) financial inclusion does not have a significant effect on personal financial management; (3) fintech cannot moderate the effect of financial literacy on personal financial management; (4) fintech is proven to moderate the effect of financial inclusion on personal financial management. These findings reveal the complexity of the dualistic role of fintech—on the one hand, it is unable to strengthen the influence of financial literacy, but on the other hand, it has succeeded in transforming financial access into better management capabilities. This study makes an important contribution to the development of financial behavior theory in the digital era and has practical implications for regulators and fintech service providers in designing more effective financial education and digital financial service strategies.